ANALISIS MANAJEMEN RISIKO KEUANGAN UNTUK MENINGKATKAN PROFIT PADA CV. DARMATA BORNEO CABANG ERO OPTIK DI BANJARMASIN - Jhony Fahrin Sapar; Periyadi Periyadi; Noorlaily Maulida (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
This study aims to analyze finance in order to increase profits at CV. Dharmata Borneo branch of ERO Optics in Banjarmasin using exchange rate risk, interest rate risk and liquidity ratio. This research method is a qualitative method. Research results and in financial risk management on CV. Dharmata Borneo branch of ERO Optics for the past three years, starting from 2019-2021, it can be seen that there are fluctuations in exchange rate risk, interest rate risk and ratios that reach. To get the exchange rate for three years starting 2019-2021 1.97%, still in the low loss category. Meanwhile, interest rate risk for three years starting from 2019-2021 is 1.50%, still in the negligible (ignored) category. And the last risk is the liquidity ratio. Starting from 2019-2021 using a ratio calculation of 206.74% the liquidity level is in the liquid category, while the quick ratio calculation is 156.43%% the liquidity level is still in the liquid category, and the cash ratio is 81.93% the liquidity level is still in the liquid category. liquid category. Financial risk analysis is still in the low category according to fluctuations in the level of existing business policies.